2017
DOI: 10.15252/msb.20177663
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic atlas of insulin signalling reveals tissue‐specific mechanisms of longevity assurance

Abstract: Lowered activity of the insulin/IGF signalling (IIS) network can ameliorate the effects of ageing in laboratory animals and, possibly, humans. Although transcriptome remodelling in long‐lived IIS mutants has been extensively documented, the causal mechanisms contributing to extended lifespan, particularly in specific tissues, remain unclear. We have characterized the proteomes of four key insulin‐sensitive tissues in a long‐lived Drosophila IIS mutant and control, and detected 44% of the predicted proteome (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 127 publications
6
56
0
Order By: Relevance
“…The level of Gnmt was elevated in the fat body of long‐lived IIS mutant flies. This is in agreement with a recent proteomic study of an independent IIS mutant (Tain et al, ) which showed fat body‐specific increases in Gnmt, suggesting that increased Gnmt levels, and thus altered Met metabolism, may be a common feature of long‐lived IIS models. Recently, Gnmt expression was found to be elevated in long‐lived dietary restricted mice (Hahn et al, ), and increased Gnmt expression is a common feature of long‐lived Ames dwarf mice (Brown‐Borg, Borg, Meliska, & Bartke, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The level of Gnmt was elevated in the fat body of long‐lived IIS mutant flies. This is in agreement with a recent proteomic study of an independent IIS mutant (Tain et al, ) which showed fat body‐specific increases in Gnmt, suggesting that increased Gnmt levels, and thus altered Met metabolism, may be a common feature of long‐lived IIS models. Recently, Gnmt expression was found to be elevated in long‐lived dietary restricted mice (Hahn et al, ), and increased Gnmt expression is a common feature of long‐lived Ames dwarf mice (Brown‐Borg, Borg, Meliska, & Bartke, ).…”
Section: Discussionsupporting
confidence: 92%
“…Studies examining the transcriptomic and proteomic changes that occur during aging, or in response to interventions that ameliorate its effects, have revealed several conserved prolongevity processes, including many metabolic changes (Afschar et al, ; Dobson et al, ; Hahn et al, ; Murphy et al, ; Narayan et al, ; Page et al, ; Stout et al, ; Tain et al, ; Teleman, Hietakangas, Sayadian, & Cohen, ). These include carbohydrate metabolism (Afschar et al, ), lipid and fatty acid metabolism (Dobson et al, ; Hahn et al, ; Murphy et al, ; Page et al, ), energy metabolism (Afschar et al, ), and protein and methionine (Met) metabolism (Narayan et al, ; Stout et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, some precedence suggests only a limited role for dfoxo as the mediator of reduced IIS in aging, as dfoxo only partially rescues longevity benefits of chico, revealing that IIS extends lifespan through some FOXO-independent pathways (Yamamoto & Tatar, 2011). On the other hand, our whole animal analysis of dFOXO targets may obscure its role in IIS signaling if IIS and FOXO regulate aging only through actions in a few specific tissues, as previously documented (Tain et al, 2017;Wolkow, Kimura, Lee, & Ruvkun, 2000). In this vein, we find that dilp2 controls thorax ERK signaling but not AKT, suggesting that dilp2 mutants may activate muscle-specific ERK/MAPK anti-aging programs, although their potential action through dFOXO remains to be determined.…”
Section: While Foxo (Dfoxo or Daf-16) Is Intimately Associated With Hmentioning
confidence: 57%
“…The mass spectrometer was operated in a data-dependent mode with survey scans from 300 to 1,700 m/z (resolution of 60,000 at m/z = 200). Up to 15 of the top precursors were selected and fragmented using higher energy collisional dissociation (HCD) with a normalized collision energy value of 28 [59]. The MS2 spectra were recorded at a resolution of 17,500 (at m/z = 200).…”
Section: Cell Analysismentioning
confidence: 99%
“…AGC target for MS and MS2 scans were set to 3E6 and 1E5, respectively, within a maximum injection time of 100 and 25 ms for MS and MS2 scans, respectively. Dynamic exclusion was enabled to minimize repeated sequencing of the same precursor ions and set to 30 s [59].…”
Section: Cell Analysismentioning
confidence: 99%